2010
DOI: 10.1111/j.1365-2966.2009.16133.x
|View full text |Cite
|
Sign up to set email alerts
|

Variability and stability in blazar jets on time-scales of years: optical polarization monitoring of OJ 287 in 2005-2009

Abstract: OJ 287 is a BL Lac object at redshift z= 0.306 that has shown double‐peaked bursts at regular intervals of ∼12 yr during the last ∼40 yr. We analyse optical photopolarimetric monitoring data from 2005 to 2009, during which the latest double‐peaked outburst occurred. The aim of this study is twofold: firstly, we aim to analyse variability patterns and statistical properties of the optical polarization light curve. We find a strong preferred position angle in optical polarization. The preferred position angle ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 91 publications
(80 citation statements)
references
References 71 publications
6
74
0
Order By: Relevance
“…Since we used filters that are slightly different from the R-band and since the polarization position angle in high polarization standards is typically wavelength-dependent, though not strongly, a small systematic error in our PA calibration was expected. We compared the derived r-band zero points to the ones derived in Villforth et al (2010) for the R-band and found the two to differ by 1.4 ± 1.3 and by 1.8 ± 1.1 degrees for the CA and NOT data, respectively. As a result, any PA offsets due to filter mismatch are likely to be smaller than 2 degrees.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Since we used filters that are slightly different from the R-band and since the polarization position angle in high polarization standards is typically wavelength-dependent, though not strongly, a small systematic error in our PA calibration was expected. We compared the derived r-band zero points to the ones derived in Villforth et al (2010) for the R-band and found the two to differ by 1.4 ± 1.3 and by 1.8 ± 1.1 degrees for the CA and NOT data, respectively. As a result, any PA offsets due to filter mismatch are likely to be smaller than 2 degrees.…”
Section: Discussionmentioning
confidence: 98%
“…Valtonen et al 2008;Villforth et al 2010;Fermi-Lat Collaboration et al 2010), polarization measurements have rarely been used to verify them. So far, only Impey & Brand (1982), Borra & Corriveau (1984), Impey & Tapia (1988), Fugmann & Meisenheimer (1988), Kuehr & Schmidt (1990), Jannuzi et al (1993a), Kock et al (1996), Marcha et al (1996), and S07 used polarization measurements as a diagnostic tool for detecting or confirming BL Lac candidates.…”
Section: General Commentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analysis also relies on the assumption that the mean EVPA represents a stable EVPA of the jet, which may not be the case considering the fairly short time span of our observations. As discussed in e.g., Villforth et al (2010) and Sakimoto et al (2013), it is also possible that the same sources occasionally show a preferred polarization angle while at another time they may not, so clearly long-term polarization observations are required to better understand this in the HSP objects.…”
Section: Preferred Polarization Anglementioning
confidence: 99%
“…In particular, for OJ287 we also found a coherent relation in the multi-spectral range behavior of the source that underwent a series to two γ-ray flares at the end of [39] (Fig. 6).…”
Section: The "Far Site" γ-Ray Emission In Flares Of Oj287mentioning
confidence: 67%